A Critical Review on the Book “Sufism and Politics in Prose Texts until the End of the 4th Century )AH(“ - Peiman Abolbashari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book “Sufism and Politics in Prose Texts until the End of the Fourth Century AH”, written by Mahdi Heidari, is a collection of eight re-published articles under the banner of a Book. The chapters of the book are based on fragile, non-historical theories and on the transcendental concept of unity and plurality and its effect on the establishment of Sufi multifaceted relations with politics. The choice of a weak hypothesis along with a lack of method has made the author lose track of the historical background and context and has caused the time and place to be lost in the text. Heidari has also made it impossible for the average audience to read the book by quoting untranslated Arabic narrations. Some generalizations of error in the classification of Sofia are prominent errors that have seriously damaged the work. In this article, an attempt has been made to critique the quality of the book, especially in terms of content analysis